Abundance and morphometry of the freshwater bivalve Prisodon obliquus at Maratauíra river, Abaetetuba, State of Pará, northern Brazil - Mara Rúbia Ferreira Barros; Renata R D Chagas; Wagner Cesar Rosa dos Santos; Valdo Sena Abreu; Rosana Esther Oliveira da Silva; Cibele Cristina Oeiras Freire; Guilherme da Cruz dos Santos-Neto; Marko Herrmann (PANGAEA, 2019)
Abundance and morphometry of freshwater mussels collected in the Maratauíra river, Abaetetuba, Pará between September 2016 and September 2017. Measuring the anteroposterior length of each individual. In all, 8,399 individuals were collected, ranging in length from 7.71 to 104.63 mm.